2013
DOI: 10.1111/ijn.12047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of poor sleep quality in Korean older adults

Abstract: The purposes of this study were to evaluate the levels of sleep quality and to examine its related factors in the elderly Korean adults. A cross-sectional research design was used, and 157 adults, aged from 65 to 89, were recruited from five community health centres in Gyeonggi province and Seoul, Korea. All participants were informed about the purpose of the study and were asked to provide demographic characteristics, chronic conditions, self-rated health, pain, depression, life satisfaction and sleep quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
32
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 31 publications
13
32
2
1
Order By: Relevance
“…These results were in line with the findings of Park et al (Park, Yoo, & Bae, 2013), Oliviera et al (Oliviera Araújo & Ceolim, 2010) and Azri et al (Azri et al, 2016), indicating 64.3% of the Korean elderly, 63.1% of the Brazilian elderly and the Indonesian elderly had poor sleep quality, respectively (Azri et al, 2016). However, Niu et al reported that 33.7% of the Chinese elderly had poor sleep quality (Niu et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results were in line with the findings of Park et al (Park, Yoo, & Bae, 2013), Oliviera et al (Oliviera Araújo & Ceolim, 2010) and Azri et al (Azri et al, 2016), indicating 64.3% of the Korean elderly, 63.1% of the Brazilian elderly and the Indonesian elderly had poor sleep quality, respectively (Azri et al, 2016). However, Niu et al reported that 33.7% of the Chinese elderly had poor sleep quality (Niu et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In their study, Park et al reported maximum level of mean sleep quality for the component scores "sleep latency" and "sleep duration" and minimum level of mean sleep quality for the component scores "use of sleep medication"; Further, the obtained results indicated that the sleep quality of the elderly was reduced with aging, but no statistically significant difference was observed, confirming the results of Niu et al (Niu et al, 2016), Kiejna et al (Kiejna, Rymaszewska, Wojtyniak, & Stokwiszewski, 2004) (Niu et al, 2016). However, the study of Park et al on the Korean elderly population showed no significant relationship between gender and sleep quality (Park, Yoo, & Bae, 2013).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…First, sleep deprivation (ie, poor quality or short duration) has been found to be negatively associated with HRQOL in HK 22 and the Spain. 21 Second, health problems in HRQOL dimensions such as physical functioning, 16,18,19 mental health, 14,17 and pain 18,20 are correlated with extreme sleep duration and poor sleep quality, which may also have negative effect on selfrated health. 36 Third, sleep problems (eg, insomnia) 10,37 or sleep complaints 38 that normally accompany sleep disturbances are reported to have a negative relationship with HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,20,22 This was determined by the education level of study participants of whom nearly half did not receive formal education. A pilot study with a small sample showed that our participants had difficulties in understanding or completing PSQI in a face-to-face interview setting.…”
Section: Discussionmentioning
confidence: 99%